Financial Status Among The Malaysian Elderly - Parsa, Bita (2008)
The increasing life expectancy phenomenon forces the people to have enough money to meet their needs in old age. Therefore the finance matter is vital for the elderly. This study aims to investigate the financial status of Malaysian elderly and its associations with social demographic characteristics, financial behavior and financial problems. This study employed a secondary data from an Intensification of Rresearch on Priority Areas (IRPA) study on Quality of Life of Older Malaysians (2003). The data was analyzed using Statistical Package of Social Science (SPSS) version 13. The procedures were descriptive statistics, t-test, chi-square test, ANOVA and multiple regression analysis. The study found that majority of the respondents had limited income and assets. About sixty percent of Malaysian elderly had negative net worth. Analysis of financial ratios showed that most of the respondents had not enough saving and liquidity assets. A significant positive correlation was found between net worth and good financial behaviour. The Multiple linear Regression (MLR) showed the elderly financial status was explained by (1) higher income, (2) house ownership, (3) higher education attainment, (4) ethnicity (Chinese), (5) good financial behaviours (6) less financial problems, (7) living arrangement, (8) employment status, and (9) household size. Since most of the elderly has lower income and moderate financial behaviour, financial education should be addressed to this population in managing their money in old age, which leads to a better quality of life among the Malaysian elderly.